Investigative Module to Eliminate EHR Redundancy (International Journal of Advanced Research in Computer Science, 2017)
Even though there are many efforts that provide mechanisms to exchange EHR between different health organizations, but reach to online EHR system have faced many challenges. Duplication data is one of the most serious problems. This problem is happened when two different health organization try to update the specific patientâ€™s EHR. Inaccurate health information leads to the main reason of inaccurate diagnosis. Developing tool that eliminate duplication data is crucial to the success any systems. This module consist of the group of components that its role to check all flowing information to EHR database. This module called Investigative module which will play very important role in online EHR. The quantity of health information is increasing every day that health organizations have a huge and very sensitive data so that the investigative module should take care of its database size. In this paper we demonstrate investigative module and how it works. For simplistic, we neglect some issues such as security mechanisms.Â Keywords: EHR; Electronic Health Record; Health information; HL7; EHR standardized; duplication data, online EHR , interoperability